الإعلان عن التشخيص ...التثلث الصبغي نموذجا - Chibani, Abdellatif; Badidi, Moulay Thami (Darul Yasin Al Sys, 2025)
This study explores the manner and method in which the diagnosis of Trisomy 21 is communicated to parents of newborns, and the extent to which this impacts the psychological responses of parents—particularly mothers. Through an objective content analysis of statements made by several mothers who received the diagnosis postnatally in an inappropriate manner, the study seeks to uncover psychological reactions that arise when such critical information is delivered abruptly, insensitively, and with little emotional consideration. The findings reveal that most mothers described the moment of diagnosis as painful and shocking, emphasizing the inadequacy of the delivery—characterized by coldness, randomness, and a lack of detailed explanation or psychological support. This led to a range of psychological reactions in response to the distressing experience, including denial, rejection, guilt, sadness, initial shock, and some psychosomatic symptoms.